Conjunctivitis due to Neisseria sicca: A case report - Ilker Eser; Alper Akcali; Muserref Tatman-Otkun; Arzu Taskiran-Comez (Indian Journal of Ophthalmology, 2014)
We report the first case, in Medline-based literature, of conjunctivitis caused by gram negative diplococcus, Neisseria sicca. Although it is not widely accepted as such, isolation from cultures of repeated eye swab samples suggests that N. sicca may be a pathogen in conjunctival infections. Positive culture for this organism should not be readily dismissed. Such conjunctivitis responded favorably to treatment with netilmicin eye drops.